Mahmoud Darwish Sebagai Penyair Dalam Konstruksi Sosial: Kajian Sosiologi Sastra Pierre Bourdieu - Selva Allaya Navika; Rohanda Rohanda; M Abdul Halim (Jurnal Ragam Pengabdian, 2026)
This study aims to identify and analyze how habitus and arena influence Mahmoud Darwish as a poet in the process of creating poetry, as well as to describe the influence of habitus and arena in the social construction of Mahmoud Darwish. This study uses a descriptive-analytical qualitative method with Pierre Bourdieu's sociology of literature approach. Data was obtained through sources in the process of tracing Mahmoud Darwish's biography and background relevant to the context of his work creation in order to maintain the relevance of the analysis to the research objectives. The next stage involved a thorough reading of three poems by Mahmoud Darwish entitled فكِّرْ بغيركَ, بطاقة هوية, and قصيدة حالة حصار obtained from the Al-Diwan website. To facilitate understanding of the meaning of each line, this study used validation by comparing several credible online sources. The research data, in the form of Mahmoud Darwish's poems and writings, were analyzed based on the concepts of habitus and arena to reveal the social construction in his work. The results of the study show that ten data points were found that represent habitus, arena, and the influence of both in shaping the social construction of Mahmoud Darwish as a poet.